The Use Of Code Mixing Applied by Maudy Ayunda in YouTube Channel - Indriyani, Furi; Aulia, Ratna; Dewi, Nurmala; Mardewi, Tati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to analyze the code mixing used by Maudy Ayunda on the Youtube Channel. Code mixing has become a recent phenomenon, and is often used by young people today in their communications. One young person who often does code-mixing in these conversations is an actress, Maudy Ayunda. This might happen because he has an educational background abroad, namely English as his first language. In this research, the writer uses descriptive qualitative method. And for the analysis of the types of code mixing used by Maudy Ayunda, the authors apply Muysken and Hoffman's theory. From Muysken's theory, code mixing is divided into three parts, namely, insertion, substitution, and congruent lexicalization. Meanwhile, from Hoffman's theory, the type of code mixing is divided into three parts, namely intra-centential, intra-lexical, and involving changes in pronunciation. The results of the analysis of the two theories produce 39 data. The most dominant type of code mixing used in videos is alternation. Keywords : Code Mixing, Type of Code Mixing, Maudy Ayunda